Modeling of minimal systems based on ATP-Zn coordination for chemically fueled self-assembly. Issue 8 (8th February 2023) - Rossi, Emma; Ferrarini, Alberta; Sulpizi, Marialore
Abstract : Binding of ATP to Zn complexes can trigger self-assembly of transient supramolecular structures. Here, we use well-tempered metadynamics simulations to elucidate the structure and energetics of binding. Abstract : Following nature's example, there is currently strong interest in using adenosine 5′-triphosphate (ATP) as a fuel for the self-assembly of functional materials with transient/non-equilibrium behaviours. These hold great promise for applications, e.g. in catalysis and drug delivery. In a recent seminal work [Maiti et al., Nat. Chem., 2016, 8, 725], binding of ATP to the metallosurfactant zinc hexadecyl-1, 4, 7-triazacyclononane ([ZnC16 TACN] 2+ ) was exploited to produce ATP-fueled transient vesicles. Crucial to the complex formation is the ability of ATP to bind to the metal ion. As a first step to unveil the key elements underlying this process, we investigate the interaction of ATP with Zn 2+ and with methyl-1, 4, 7-triazacyclononane ([ZnCH3 TACN] 2+ ), using all-atom molecular dynamics simulations. The free energy landscape of the complex formation is sampled using well-tempered metadynamics with three collective variables, corresponding to the coordination numbers of Zn 2+ with the oxygen atoms of the three phosphate groups. We find that the structure of the ternary complex is controlled by direct triphosphate coordination to zinc, with a minor role played by the interactions between ATP and CH3 TACN which, however, may be important for the build-up of supramolecular assemblies.